Indonesia : Eighth Review Under the Extended Arrangement and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report, 2003)
The discussions focused on advancing the unfinished reform agenda, and strengthening the investment climate. The macroeconomic objectives for 2003 remain broadly unchanged from those presented at the seventh review. Discussions on the 2004 financing outlook focused on the implications of the authorities' intention at this stage not to seek recourse to exceptional financing. The authorities agreed with the importance of maintaining momentum and forcefully addressing the unfinished structural reform. Progress is being made in strengthening Indonesia's antimoney laundering (AML) framework.